Manure and Light Intensity Affect Growth Characteristics and Essential Oil of Peppermint (Mentha piperita L.). Issue 8 (16th November 2016) - Mousavinik, Seyed Mohsen; Asgharipour, Mohammad Reza; Sardashti, Sara
Abstract: The utilization of organic fertilizer is an effective method in production of medicinal plants because of its beneficial effects on soil structure, reduction of environmental problem and plant growth improvement. The experiment was conducted in a research field at the University of Zabol at the Zabol, Iran, to determine the effects of manure (without manure, 30 and 40 t ha-1) and light intensity (full sunlight, 80 % of sunlight, 60 % of sunlight, 40 % of sunlight and 20 % of sunlight) on peppermint yield and quality. The results showed that the treatments significantly affected all studied traits. The highest fresh and dry weight and leaf area obtained from 80 % of sunlight and 40 t ha-1 manure and the lowest amount of them obtained from 20 % of sunlight and 40 t ha-1 manure. The highest essential oil content was belong to 60 % of sunlight and 30 t ha- 1 manure and the lowest was belong to 20 % of sunlight and 40 t ha-1 manure. Among the essential oil compositions, the highest mentol content obtained from 20 % of sunlight and the highest content of menton obtained from 80 % of sunlight. It seems that rational application rate of manure (e.g. 30 t ha-1 manure) under suitable radiation conditions (60 % of sunlight) can maintain higher yield and essential oil content of peppermint. Therefore, the enough radiation with a rational manure application rate could be an important pathway toward sustainable production of peppermint.